Jogar um jogo! Brincar (talvez de uma brincadeira): conceitos e formação de professores - Melo, Lucas Lannes Machado de (Universidade Federal de São Carlos, 2025)
Games and play are primitive cultural manifestations, but they are still little valued in Western societies. Several authors from European countries and the Americas strive to raise awareness about the importance of play. In Physical Education and Pedagogy courses, these phenomena are studied, sometimes as synonyms, sometimes as similar but distinct. By reviewing the basic or complementary bibliography of the disciplines that deal with games and play in these courses at the three largest universities in the State of São Paulo: USP, Unicamp and UFSCar, this text seeks to observe the theoretical concepts that are being disseminated. By researching more recent academic articles, it seeks to update the discussion and defend free play in schools, in relation to teacher training. Finally, it deliberates on linguistic differentiation, since the Portuguese language understands the two terms as distinct, while the original references were written in languages that do not have distinct terms for these phenomena.
Play a game! Play (maybe a play): concepts and teacher education
Keywords: Jogo; Brincadeira; Livre Brincar; Formação de Professores; Game; Play; Free Play; Teacher Education; CIENCIAS HUMANAS::EDUCACAO